(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this article, we will consider the words related to the field of information technology that are often used in our speech today. Also, the units related to this branch, which is rapidly developing today, are analyzed grammatically and the methods of their formation are revealed through several examples